2017
DOI: 10.1186/s12879-017-2208-0
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of brucellosis in abattoir workers at Debre Zeit and Modjo export abattoir, Central Ethiopia

Abstract: BackgroundBrucellosis is one of the major zoonoses globally with great veterinary and public health importance, particularly in developing countries where people are having frequent contact with livestock and animal products. This cross sectional study was carried out from November 2013 to May 2014 to determine the seroprevalence and assess the potential risk factors of brucellosis in abattoir workers of five export abattoirs at Debre Ziet and Modjo, Central Ethiopia.MethodsSerology and structured questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
17
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 15 publications
8
17
2
Order By: Relevance
“…A total of 292 individuals working in slaughterhouses were described as brucellosis-positive in fourteen articles [19,20,23,33,34,[41][42][43][44][45][46][47][48][49]. Most of those individuals were from America (n = 162), Africa (n = 60), and Europe (n = 37) and the minority from Asia (n = 33).…”
Section: Abattoir Workersmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 292 individuals working in slaughterhouses were described as brucellosis-positive in fourteen articles [19,20,23,33,34,[41][42][43][44][45][46][47][48][49]. Most of those individuals were from America (n = 162), Africa (n = 60), and Europe (n = 37) and the minority from Asia (n = 33).…”
Section: Abattoir Workersmentioning
confidence: 99%
“…The main type of pathogen exposure reported was contact with animal fluids, aborted fetus, placenta and viscera. Accidental contact with those materials was described in three studies: in Spain and Ethiopia, 12.26% (13/106) and 48.72% (76/156) of slaughterhouse workers, respectively, reported cutting themselves with dirty sharp blades [45,46], and in China, 100.00% (3/3) of pharmaceutical employees, who worked processing sheep placenta, reported having splashed animal fluids on their faces [47]. The great occurrence of direct contact with biological contaminated fluids aroused the interest of several authors to understand which PPE were used or not by this group of professionals (Table 2).…”
Section: Abattoir Workersmentioning
confidence: 99%
“…The human seropositive case reported in this study was from the group of cleaners. Swai and Schoonman (2009) and Tsegay et al (2017) argued that cleaners in the abattoir being the least educated group may lack knowledge on how brucellosis is transmitted. On the other hand, since they are most heavily involved in handling and disposing all condemned abattoir materials including aborted foetuses that usually have very high concentrations of Brucella pathogens; they are at a much higher risk of infection when compared to other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Serologic studies performed in other countries presented differing proportions of human brucellosis seroprevalences among slaughterhouse workers. For instance, a Nigerian study found that the brucellosis seroprevalence was 59.3% among butchers [ 27 ], while an Ethiopian study found that the seroprevalence in abattoir workers, as determined by the Rose Bengal plate test, was 4.7% [ 28 ]. Additionally, the brucellosis seroprevalence was reported to be 10.3% (using SAT) in Uganda and 7.9% (using ELISA) in Iran [ 11 , 29 ].…”
Section: Discussionmentioning
confidence: 99%